The allocentric neglect due to injury of the inferior fronto-occipital fasciculus in a stroke patient: A case report. Issue 2 (January 2018) - Jang, Sung Ho; Jang, Woo Hyuk
Abstract: Rationale: We report on a patient who developed allocentric neglect due to injury of the inferior fronto-occipital fasciculus (IFOF) following intracranial hemorrhage, diagnosed using diffusion tensor tractography (DTT). Patient concerns: Her cognition seemed normal (A 17-year-old, right-handed female patient). However, in spite of a normal visual field, her perception was missing on the left side, and she had no awareness of her deficit. She was unable to perceive the left side in each of 2 objects, regardless of position of the 2 objects, and failed at detail exploration of the left side of 1 object. In addition, the line bisection test, the most representative neglect test, did not reveal any abnormality. Diagnoses: She was diagnosed with an intracerebral hemorrhage (right thalamus), intraventricular hemorrhage, and subarachnoid hemorrhage due to arteriovenous malformation in the right thalamus. Interventions: Seven weeks after onset, she began rehabilitation. Consequently, the apple cancellation test to discriminate between allocentric and egocentric neglect was performed, with the result of severe allocentric neglect. Outcomes: The right superior longitudinal fasciculus and inferior longitudinal fasciculus were well-reconstructed without definite injury compared with those of the left side. However, the right IFOF was discontinued in the anterior portion around the frontal lobe. Lessons: Allocentric neglect due to injury of IFOF was demonstrated in a stroke patient using DTT. It appears that DTT would be helpful in demonstrating the neglect type and pathway in patients with neglect.